2008
DOI: 10.2527/jas.2007-0515
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and sensory properties of beef of known source and finished on wet distillers grains diets containing varying types and levels of roughage1,2,3

Abstract: ABSTRACT:Beef knuckles (n = 160) were obtained from source-verified cattle finished on 30% wet distillers grains plus solubles enriched with varying levels of alfalfa hay (4 or 8%), corn silage (6 or 12%), or corn stalks (3 or 6%) based on NDF. Proximate analysis, pH, oxidation-reduction potential, fatty acid composition, and sensory analysis were conducted on the rectus femoris muscle to determine if roughage inclusion, in conjunction with wet distillers grains plus solubles and cattle source, affects beef fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…Protein and lipid contents were similar {P > 0.13) among treatments. Similar results were reported by Jenschke et al (2008), who foiuid no differences in the moisture, protein, or lipid content in beef when steers were fed wet distillers grains with alfalfa hay, corn stalks, or corn silage, indicivting that concentration of distillers grains in the diet has no effect. As well.…”
Section: Proximate Analysissupporting
confidence: 88%
“…Protein and lipid contents were similar {P > 0.13) among treatments. Similar results were reported by Jenschke et al (2008), who foiuid no differences in the moisture, protein, or lipid content in beef when steers were fed wet distillers grains with alfalfa hay, corn stalks, or corn silage, indicivting that concentration of distillers grains in the diet has no effect. As well.…”
Section: Proximate Analysissupporting
confidence: 88%
“…The influence of fatty acids in meat flavor was studied by Jenschke et al (2008), who observed that when the percentage of C 18:2 n-6 increased, the unpleasant flavor decreased, while when the concentration of C 18:2 cis 9 -trans 11 and C 20:1 n-9 increased, the unpleasant flavor was more evident. LaBrune et al (2008) reported that a lipid-rich diet with flaxseed increases the percentage of linoleic acid without changing the flavor.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the diff erences in fi ber (cell wall) analysis makes the general term "roughage," frequently used as an inclusive undefi ned term in the ruminant animal sector, rather meaningless. Yet roughage remains a common term as roughage is roughage and remains prevalent in the current animal literature (Crawford et al, 2008;Golden et al, 2008;Jenschke et al, 2008) including nutritional requirements for cattle (National Research Council, 2000). Diff erences in the roughage component of an animal's diet, however, can greatly limit one's ability to extrapolate data among experiments that have otherwise identical or similar ration compositions.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…The results to be of value to the feeder can best be obtained by measurements made in the form of pounds of milk, meat, or other animal products.” In addressing the latter situation, Morse (1913) noted that, “we need to know the kind of protein, carbohydrate, fat, and ash concentrations of feeds, as well as total amounts.” Nearly 100 yr later this dual level of interest and concern, that is, “what if” and “why,” remains pertinent in the evolving process of providing a better grasp of the chemistry of herbage (grazed or stored) as an animal feed with an understanding of how each chemical entity meets the animals needs. This interest became a segue for the emergence in the United States by the late 1860s of the Weende system of proximate analysis that was developed at the Weende Experiment Station near Gottingen, Germany (Henneberg and Stohmann, 1860, 1864). At about the same time the land grant system was emerging in the United States and colleges of agriculture were being born with departments of animal industry and agricultural crops.…”
mentioning
confidence: 99%